Load Unloading Equipment, Workers (Longshormen), and Ship Service to Performance of General Cargo Loads Unloading in Terminal Jamrud Port of Tanjung Perak, Surabaya - Titiek Suntari; Bambang Suryantoro; Mudayat Mudayat; Soedarmanto Soedarmanto (APMBA (Asia Pacific Management and Business Application), 2020)
The port is a node from the transportation system chain and is a gateway for sea transportation in the activities of sea traffic is increasing demanded in the globalization.  Loading and unloading equipment, Workers/ longshormen, and Ship Service are the parts that determine the performance of loading and unloading of general cargo in this sense is for  Jamrud terminal port of Tanjung Perak, Surabaya, the second largest port in Indonesia. This research was conducted with the aim to determine whether there is a relationship (correlation) and the influence of loading and unloading equipment, workers/ longshormen, and ship services on the performance of loading and unloading general cargo at the terminal so that it can be used as a means of performance of the terminal more efficiently and efficiently in handling loading and unloading. The method used is a quantitative method with primary data analysis in the form of numbers through the distribution of questionnaire data (Likert scale) analyzed.  The results indicated that there was a positive correlation or correlation and significant influence for the relationship of loading and unloading equipment, workers/ longshormen, and ship service  simultaneously on loading and unloading performance and correlate significant. This shows that there is a positive and significant correlation between loading and unloading equipment, workers/ longshormen, and ship services to the loading and unloading performance at the Jamrud terminal. Therefore, to improve the performance of loading and unloading general cargo at the terminal port of Tanjung Perak, Surabaya must pay attention to these three factors.